2023
DOI: 10.1016/j.gpb.2023.02.003
|View full text |Cite
|
Sign up to set email alerts
|

RNA Methylome Reveals the m6A-Mediated Regulation of Flavor Metabolites in Tea Leaves under Solar-Withering

Abstract: The epitranscriptomic mark N6-methyladenosine (m6A), which is the predominant internal modification in RNA, is important for plant responses to diverse stresses. Multiple environmental stresses caused by the tea-withering process can greatly influence the accumulation of specialized metabolites and the formation of tea flavor. However, the effects of the m6A-mediated regulatory mechanism on flavor-related metabolic pathways in tea leaves remain relatively uncharacterized. We performed an integrated RNA methylo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 75 publications
2
27
0
Order By: Relevance
“…Although m6A has been the focus of many studies in recent years, our knowledge about the effects of m6A on the secondary metabolites is limited. To explore the effects of the m 6 A on flavor-related metabolic pathways in tea leaves of Camellia sinensis, a recent study indicated that CsALKBH4-driven RNA demethylations can directly affect the accumulation of volatile terpenoids and indirectly influence the flavonoid, catechin, and theaflavin contents . Our study revealed that 12 RNA modifications, including m6A, were related to AFB1 production in A.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Although m6A has been the focus of many studies in recent years, our knowledge about the effects of m6A on the secondary metabolites is limited. To explore the effects of the m 6 A on flavor-related metabolic pathways in tea leaves of Camellia sinensis, a recent study indicated that CsALKBH4-driven RNA demethylations can directly affect the accumulation of volatile terpenoids and indirectly influence the flavonoid, catechin, and theaflavin contents . Our study revealed that 12 RNA modifications, including m6A, were related to AFB1 production in A.…”
Section: Discussionmentioning
confidence: 63%
“…To explore the effects of the m 6 A on flavor-related metabolic pathways in tea leaves of Camellia sinensis, a recent study indicated that CsALKBH4driven RNA demethylations can directly affect the accumulation of volatile terpenoids and indirectly influence the flavonoid, catechin, and theaflavin contents. 87 Our study revealed that 12 RNA modifications, including m6A, were related to AFB1 production in A. flavus (Figure 1), which is one of the most important secondary metabolites in A. flavus. This study lays the foundation for revealing the biological function of RAN epigenetic modification in the regulation of fungal secondary metabolism.…”
Section: Discussionmentioning
confidence: 68%
“…Various abiotic stresses during the withering process have greatly affected the accumulation of tea metabolites, thus promoting the formation of tea quality and flavor. 4 As for the study of withering methods, some scholars have studied the effect of sunlight withering on the quality of tea, starting with the taste and aroma substances of tea, and analyzed the changes of short-time sunlight-withered leaves. They found that the taste of sunlight-withered leaves became stronger, and the aroma of tea changed from a clear odor to floral and delicate fragrance.…”
Section: Introductionmentioning
confidence: 99%
“…So far, there has been some progress in the research on the withering process of various kinds of tea. Various abiotic stresses during the withering process have greatly affected the accumulation of tea metabolites, thus promoting the formation of tea quality and flavor 4 . As for the study of withering methods, some scholars have studied the effect of sunlight withering on the quality of tea, starting with the taste and aroma substances of tea, and analyzed the changes of short‐time sunlight‐withered leaves.…”
Section: Introductionmentioning
confidence: 99%
“…These multiple abiotic stresses stimulate tea leaves to produce large amounts of secondary metabolites to help protect themselves against external stresses, and on the other hand these produced secondary metabolites improve the aroma and taste of the tea leaves (Zhu et al, 2023).…”
Section: Introductionmentioning
confidence: 99%